2017
DOI: 10.1111/jmi.12516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prior deformation on microstructural development and Laves phase precipitation in high‐chromium stainless steel

Abstract: This study investigated the influence of deformation on precipitation behaviour and microstructure change during annealing. Here, the prior deformation of high-chromium stainless steel was tensile deformation of 3%, 6% and 10%, and the specimens were then annealed at 700˚C for 10 h. The specimens were subsequently analyzed using backscattered electron image and electron backscattering diffraction measurements with SEM. Compared with the deformation microstructure, the grains revealed no preferred orientation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…5(c). Similar results highlighting local plastic deformation with regard to the analysis of IPF data were shown by Hsiao et al (Ref 34,35) and Schayes et al (Ref 23). Furthermore, the average KAM value for the deep rolled condition increased to 0.91°as detailed in Fig.…”
Section: Discussionsupporting
confidence: 86%
“…5(c). Similar results highlighting local plastic deformation with regard to the analysis of IPF data were shown by Hsiao et al (Ref 34,35) and Schayes et al (Ref 23). Furthermore, the average KAM value for the deep rolled condition increased to 0.91°as detailed in Fig.…”
Section: Discussionsupporting
confidence: 86%
“…One of the alloys originally developed for the application in SOFCs is so-called Crofer 22 H, which is a commercially available 22Cr ferritic steel containing some (Nb,W)(Fe,Cr) 2 Laves phase, see, for example, [759,762,763,772,773]. Due to its promising high-temperature mechanical properties, the idea came up to modify and optimize this Laves phase forming, fully ferritic steel for structural applications at 600 to 650°C in power plants [774][775][776][777].…”
Section: Ferritic 15-22% Cr Steelsmentioning
confidence: 99%
“…Liang et al [8,12] created a large number of LAGBs in Fe-13Cr-5Al-2Mo-1Nb alloy through warm-rolling and studied the effect of annealing time. Hsiao et al [52] also observed the LAGBs in high-chromium stainless steel and found that the amount of LAGBs increased with the increase in deformation. Liu et al [9] found that the amount of LAGBs in the FeCrAl alloy decreased with the increase in deformation at 1100 °C because of the occurrence of DRX.…”
Section: Grain Boundary Featurementioning
confidence: 97%